TASP1 Promotes Gallbladder Cancer Cell Proliferation and Metastasis by Up-regulating FAM49B via PI3K/AKT Pathway - Zhang, Yijian (Int J Biol Sci, 2020)
The highly conserved protease TASP1 not only takes part in critical site-specific proteolysis, but also plays an important role in numerous liquid and solid malignancies. However, the TASP1 expression and its biological regulation function in malignant gallbladder carcinoma (GBC) remain fully unknown. Here we observed that TASP1 levels were substantially overexpressed in GBC samples compared with non-tumor tissues. High TASP1 level was closely associated with T stage and metastasis, and was also correlated with poor prognosis in GBC patients. The depletion of TASP1 inhibited GBC cell proliferation and metastasis in vitro and in vivo. Furthermore, we first revealed that FAM49B had biological function and was positively regulated by TASP1 activating PI3K/AKT signaling pathway in GBC. At the same time, FAM49B also promoted GBC cell proliferation and migration. Inhibition of PI3K/AKT with LY294002 or FAM49B expression abrogated Myc-TASP1/Lv-shTASP1-induced GBC cell proliferation and motility. In conclusion, these findings demonstrate that TASP1 is critical for GBC progression via TASP1-PI3K/AKT-FAM49B axis and it may be a novel prognostic factor. The therapeutic targeting TASP1 may be a potential treatment approach for GBC patients.